Application of Mamdani’s Fuzzy Inference System in the Diagnosis of Pre-eclampsia - Estevania Daonce Mau; Grandianus Seda Mada; Maria Julieta Esperanca Naibili; Siprianus Septian Manek; Wasim Raza (Universitas Bumigora, 2023)
Pre-eclampsia is the second of the top three causes of death in pregnant women after bleeding and followed by infection. By knowing the risk factors, early detection of pre-eclampsia in pregnant women needs to be done so that later it can be treated more quickly to prevent further complications. This study aims to design a practical application of a decision-making system for the diagnosis of pre-eclampsia in pregnant women using the Fuzzy Inference System (FIS) method so it can be used efficiently and effectively for the early diagnosis of pre-eclampsia. The method used in data analysis is the FIS Mamdani method with defuzzification using the centroid method. The designed system considers blood pressure and proteinuria as input variables and pre-eclampsia status as output variables. The research results show that the system has 7.27% of Mean Absolute Percentage Error (MAPE) value and when comparing the final diagnosis of the system and expert diagnoses (doctors) from 20 patients at two hospitals, it was found that the system diagnosis was 100% in accordance with the expert diagnoses.